2022
DOI: 10.3390/ani12243518
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Roles of Medium and Small Carnivores in the Terrestrial Animal Community in Liancheng National Nature Reserve, China

Abstract: It is vitally important to understand the ecological roles of medium and small carnivores in the context of the massive decline in the number of large carnivores around the world. Based on a spatial association network of terrestrial birds and mammals, this study analyzed the ecological roles of medium and small carnivores in the community in Liancheng National Nature Reserve. From October 2019 to June 2020, we obtained 3559 independent detections of 20 terrestrial birds and mammals from 112 camera traps. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…According to Su et al (2022), all of the carnivorous species mentioned have the potential to prey on grounddwelling birds, including pheasants. Khoewsree et al (2022) reported a significant spatial and temporal overlap between the RJF and SFB with Dhole in Khao Yai National Park.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Su et al (2022), all of the carnivorous species mentioned have the potential to prey on grounddwelling birds, including pheasants. Khoewsree et al (2022) reported a significant spatial and temporal overlap between the RJF and SFB with Dhole in Khao Yai National Park.…”
Section: Discussionmentioning
confidence: 99%
“…In the geographical map with a scale of 1:50,000, each grid cell covers an area of 1 square kilometer. For the deployment of camera traps, one camera trap set was installed per grid cell (Su et al 2022). The camera trap positions in each grid cell were spaced more than 500 meters apart to ensure independence in capturing images (Selvan et al 2013).…”
Section: Data Collectionmentioning
confidence: 99%